ANALISIS KAWASAN EKOWISATA DAN PEMULIHAN BERBASIS KEBENCANAAN DI WISATA ALAM CITAMIANG KABUPATEN BOGOR - Dea Herwanda; I Made Adhi Gunadi; Sarojini Imran (Sekolah Tinggi Pariwisata Sahid Surakarta, 2022)
Various destinations in Indonesia are often located in the area that vulnerable to natural disasters, such as Citamiang, an ecotourism destination in Cisarua District, Bogor Regency. Back in early 2018, Citamiang had experienced landslides and flash floods, which gave a considerable impact on the area with changes in the site and damage to attractions and tourist facilities. The purpose of this study was to identification the condition of ecotourism in Citamiang and to determine disaster recovery efforts based on disaster mitigation. This study uses a qualitative method, and data is collected through observation, in depth interviews and documentation. The results showed that the tourism area of Citamiang is already in accordance with the principles of ecotourism. This can be seen from the condition of the destination component which consists of attractions, accessibility, amenities and ancillary. For the disaster recovery efforts through mitigation, the management has carried out disaster mitigation in physical development. In terms of awareness and capacity building related to disasters, the management already has awareness and initiative in disaster mitigation but it is not yet optimal. The implication is that the stakeholders managing ecotourism areas need to implement disaster mitigation aspects comprehensively in their development plans.